Thoracoscopic Repair of Congenital Diaphragmatic Hernia in Preterm Neonate at 1 Kilogram - Muhammad Choudhry; Simona Rusu; Peter Brooks; Enitan Ogundipe; Shu-Ling Chuang (Georg Thieme Verlag KG, 2021)
We report the first successful primary thoracoscopic repair of congenital diaphragmatic hernia (CDH) in a preterm infant born at 28 weeks of gestation weighing 1,043 g. Left-sided CDH was incidentally diagnosed on postnatal chest X-ray on day 1. The neonate subsequently underwent thoracoscopic repair with primary closure of the defect on day 8 weighing 1,150 g. Intraoperative arterial blood gas monitoring including end tidal carbon-dioxide remained within normal range throughout. Postoperative recovery was uneventful. One year neurodevelopmental outcome was normal for age with no CDH recurrence.